Analisis Karakteristik Organisasi dan Gaya Manajemen serta Pengaruhnya terhadap Orientasi Kewirausahaan dan Kinerja Perusahaan (Studi pada Usaha Kecil Sandang di Jawa Timur) - Sri Muljaningsih; Djumilah Zain; Kusuma Ratnawati; Made Sudarma (Jurnal Aplikasi Manajemen, 2012)
Many companies have been affected by the economics crisis, including high inflation rates, large number of bankrupt companies that lead  to fire the employess dan the choice of big companies to become small indutry that incompete to improve the performance in terms of the increase in sales and profitability. Based on this fact, purpose of this research is to identify and measure (1) the influence of Organization Characteristics towards Entreprenurial Orientation, (2) the influence of Organization Characteristics towards Company's Performance, (3) the influence of Management Style towards Entreprenurial Orientation, (4) the influence of Management Style towards Company's Performance, (5) the influence of Entreprenurial Orientation towards Company's Performance. Using 169 small industries from 7 (seven) cities/regencies in East Java with 135 respondents as the samples, and Structural Equation Modelling (SEM) with support of AMOS ver. 5.0 in analysing data, we find that the organization characteristics as reflected in a good communication betwen employers dan employee and also constant monitoring to the employees work improvement increasr the sales growth and the accuracy in taking risk. However, organization characteristics can indirectly influence the company performance without high enterpreneurial orientation. On the other hand, the opportunity given to employess to be more innovative can increase their sense of belonging and comitment to increase the employees performance. Besides, high entrepreneurial orientation can intensify the competition spirit so aggressive that manager is more innovative and proactive in taking bussiness oppurtunities which affect the improvement of bussiness. The performance of small industries in East Java is not only succeeded by team work but also by leadership which can approach the employees to be more responsible to their work.Keywords : Organization Characteristics, Management Style, Entrepreneurial Orientation and Performance.